2019
DOI: 10.5433/1679-0359.2019v40n6supl2p3123
|View full text |Cite
|
Sign up to set email alerts
|

Neospora caninum: soroepidemiologia de vacas e cães de propriedades leiteiras de Cunha, São Paulo, Brasil

Abstract: Neosporosis, a parasitic disease prevalent worldwide, is caused by the protozoan Neospora caninum, an obligatory intracellular parasite that can cause abortions and infertility in females, resulting in high economic losses. The aim of this study was to determine the seroprevalence of antibodies against N. caninum in dairy cattle, and the occurrence of antibodies in dogs from farms in the municipality of Cunha, São Paulo, Brazil. Additionally, eighteen months after the primary study, an analysis to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The seroprevalence observed for N. caninum in this study was 41.6%, while the seroprevalence of N. caninum obtained via IFA ranged from 14.1% to 97.2% in Brazil ( Guimarães et al, 2004 ; Albuquerque et al, 2005 ; Ogawa et al, 2005 ; Benetti et al, 2009 ; Camillo et al, 2010 ; Silva et al, 2015 ; Chiebao et al, 2015 ; Klauck et al, 2016 ; Katto et al, 2017 ; Fávero et al, 2017 ; Snak et al, 2018 ; Bastos et al, 2019 ; Santos et al, 2020 ; Azevedo et al, 2021 ; Souza et al, 2022 ) and 12.4% to 43.1% in other parts of the world ( Moore et al, 2002 , 2009 ; Puray et al, 2006 ; González-Warleta et al, 2008 ; Eiras et al, 2011 ; Qian et al, 2017 ; Serrano-Martínez et al, 2007 ). Some of these studies used different cut-offs in their IFA, and several studies that involved the use of IFA as a serological technique have been conducted in Brazil.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The seroprevalence observed for N. caninum in this study was 41.6%, while the seroprevalence of N. caninum obtained via IFA ranged from 14.1% to 97.2% in Brazil ( Guimarães et al, 2004 ; Albuquerque et al, 2005 ; Ogawa et al, 2005 ; Benetti et al, 2009 ; Camillo et al, 2010 ; Silva et al, 2015 ; Chiebao et al, 2015 ; Klauck et al, 2016 ; Katto et al, 2017 ; Fávero et al, 2017 ; Snak et al, 2018 ; Bastos et al, 2019 ; Santos et al, 2020 ; Azevedo et al, 2021 ; Souza et al, 2022 ) and 12.4% to 43.1% in other parts of the world ( Moore et al, 2002 , 2009 ; Puray et al, 2006 ; González-Warleta et al, 2008 ; Eiras et al, 2011 ; Qian et al, 2017 ; Serrano-Martínez et al, 2007 ). Some of these studies used different cut-offs in their IFA, and several studies that involved the use of IFA as a serological technique have been conducted in Brazil.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies showed that younger animals had a lower seroprevalence than animals above 24 months of age. The time period for which these animals had contact with a contaminated environment probably increased their chances of infection ( Bastos et al, 2019 ; Dyer et al, 2000 ; Guimarães et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%